PostgreSQL 9 high availability cookbook : over 100 recipes to desin and implement a highly available server with advanced features of PostgreSQL - Thomas, Shaun M. (Quick answers to common problems., 2014)
A comprehensive series of dependable recipes to design, build, and implement a PostgreSQL server architecture free of common pitfalls that can operate for years to come. Each chapter is packed with instructions and examples to simplify even highly complex database operations. If you are a PostgreSQL DBA working on Linux systems who want a database that never gives up, this book is for you. If you've ever experienced a database outage, restored from a backup, spent hours trying to repair a malfunctioning cluster, or simply want to guarantee system stability, this book is definitely for you.